"Infrastructure for Asian connectivity / edited by Biswa Nath Bhattacharyay, Masahiro Kawai and Rajat M. Nag" - "Bhattacharya, Biswa Nath (ed.);Kawai, Masahiro (ed.) ;Nag, R" (Cheltenham, 2012)
This book addresses the prospects and challenges concerning both soft and hard infrastructure development in Asia and provides a framework for achieving Asian connectivity through regional infrastructure cooperation towards a seamless Asia.
Keywords: Infrastructure development-Asia